The Role Of Leaders In Implementing The Company's Code Of Ethics - Widya Ginting; M Chaerul Rizky; Yesi Rahmawati; Arfana Fanditia Lubis; Herdika Fauzan Ginting (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the role of leaders in implementing a corporate code of ethics and its impact on organizational culture and sustainable corporate governance. A code of ethics is a moral and professional guideline that directs individual and organizational behavior in conducting business activities. However, the effectiveness of a code of ethics is largely determined by the role of leaders as directors, role models, and controllers of ethical behavior within the organization. The research method used is a literature study with a descriptive qualitative approach to scientific journals, books, and relevant academic publications. The results of the study indicate that leaders have a strategic role in formulating, socializing, enforcing, and evaluating a corporate code of ethics. Ethical leaders are able to build a strong tone at the top, increase employee compliance, and shape an organizational culture of integrity. This study also integrates the thoughts and findings of Muhammad Chaerul Rizky regarding leadership, human resources, and organizational ethics as a basis for analysis.